Analisis Kepuasan Kerja Guru terhadap Praktik Manajemen SDM Menggunakan Importance Performance Analysis di Yayasan Pendidikan XYZ - Sulistyani, Lusia Tuti; Aryanto, Riza (Research Center and Case Clearing House PPM School of Management, 2024)
The world of education has the most significant composition of human resources, namely teachers, who have an essential role in achieving the success of educational goals. The right HR management strategy is needed to produce performance according to organizational expectations. Employee satisfaction with the implemented HR management practices influences the achievement of HR performance. This study aimed to determine teacher satisfaction with the HR management practices of the XYZ educational foundation. This study uses descriptive quantitative methods and data collection methods using surveys. Analysis of survey results using the Importance Performance Analysis (IPA) method to determine the importance and performance/implementation of HR management practices in XYZ educational foundation. The study results stated that implementing recruitment and selection management at the XYZ educational foundation exceeded employee expectations, and HR development management was maintained. In contrast, performance management and compensation received priority for improvement. XYZ educational institutions can use the findings from this study to improve HR management strategies to increase teacher-employee satisfaction, improve teacher performance, and achieve the foundation's goalsDOI: https://doi.org/10.34149/jmbr.v21i1.485